Pengembangan Usaha Warung Kopi Untuk PeningkatanKualitas, Kuantitas Dan Produktivitas Wirausaha Kopi Di Kelurahan Karang Besuki Kecamatan Sukun - Kusubakti Andajani; Endang Sri Andayani; Retno Wulandari (STIE Malangkucecwara, 2022)
Indonesia is the fourth largest coffee producing country in the world. The development of a coffee shop business is very urgent to implement because the role of MSMEs is very large in supporting the national economy as well as playing a major role in overcoming unemployment in the community. Until 2018, MSMEs still controlled the market share in Indonesia of 99.99% with the number of business units amounting to 56,534,592 units is inversely proportional to large businesses which only control 0.01% market share with a total of 4,968 business units. This also shows that the unemployment rate in Indonesia can be absorbed more in the MSME sector. The problems agreed upon with Mbak Iin's Mbak Coffee Shop SMEs are: (1) the production aspect and (2) the economic aspect. Based on the results of the meeting and coordination with Mbak Iin's Mbak Iin Coffee Shop, it was agreed that the problem would be resolved by the following methods: (1) Coffee Entrepreneur Productivity and Welfare Improvement Program which includes: cup sealer design, espresso and capuccino machine design, coffee grinder machine design , lay out and repair coffee drink production facilities, lay out and repair coffee shops for consumers, lay out and repair fried food production facilities and (2) MSME Development Program which includes: business management training, production management training, marketing training, planning training production, financial management training, inventory training, marketing training, and HR management training.